Physical activity and fitness of physiotherapists - Adamczyk, Jakub Grzegorz; Boguszewski, Dariusz; Debrzak-Adamczyk, Ilona; Ochal, Andrzej (Polish Journal of Public Health, 2011)
Introduction. Physical activity should accompany man throughout the entire life in order stimulate correctly the development of the whole organism. The progress in medicine development isn’t a sufficient alternative in the fight against civilization diseases. Only the systematic physical activity lets people minimize their risks. Aim. Determining the significance of physical fitness in the work of physiotherapists and confronting their fitness with the declared level of physical activity. Material and methods. The research covered a group of 123 physiotherapists who were divided into five age-groups (up to 25 years, 26-30 years, 31-40 years, 41-50 years, over 50 years). The author’s questionnaire about the physical fitness and an IPAQ short version questionnaire were used in the work. Results. About 97% of respondents claim that the physical fitness is an important or very important element of the physiotherapists’ work. Majority of the studied group (93.5%) subjectively judged their health as good or very good. These results are strongly correlating with the subjective evaluation of the own physical fitness. Over half of respondents (52.0%) determined their physical fitness as good, and one-quarter (26.8%) claimed that their efficiency was on the average level. With age physical activity increased in the examined groups. The observed activity level among the oldest physiotherapists was the highest of all analysed. As the only one, this group reached the high level of physical activity according to IPAQ standards. Conclusions. Physical activity of physiotherapists was on the acceptable level, however for their patients they are a natural model of a healthy lifestyle, so the demands in relation to towards them should be higher. The key elements of the physical fitness in the work of the physiotherapist are: motor coordination, strength and endurance. While planning their own activity physiotherapists must include training in these areas. Universities should put stronger emphasis on shaping pro-healthy habits of their students.